Comparison of Outcomes of Recorded Lecture and Hands-on Course Education in Orthodontic Cast Analysis - Feyza Ulkur; Derya Germec-Cakan; Fulya Ozdemir (Galenos Yayinevi, 2015)
Purpose:The aim of this study was to compare recorded lecture education (RLE) and hands-on course education (HCE) via the test of orthodontic cast analysis lesson, which is prepared according to the Structure of the Observed Learning Outcomes (SOLO) taxonomy.Methods:In our single-blinded, randomized, cross-sectional study, 87 students (45 female, 42 male) were divided into 2 groups. In the first group, HCE was used; the second group was given an RLE. One week later, 5 questions prepared by SOLO taxonomy were given to both groups. For scores of intergroup comparisons, the Mann-Whitney U test was used, and for intragroup comparisons, the Kruskal-Wallis test was used.Results:There was no statistically significant difference between the groups' gender distribution (p.0.05). Examination scores of girls and boys did not differ significantly (p.0.05). There was a statistically significant difference in the comparison of average of scores in the HCE group (p,0.05). There was also a statistically significant difference in the average of scores of the RLE group. The averages of scores of the HCE group were found to be significantly higher than RLE group scores (p,0.05), excluding the first, fourth, and fifth questions.Conclusion:Hands-on course education, to which the students are accustomed and with which students are more comfortable asking questions in the classroom and expressing their opinions easily, have higher success rates when compared with RLE.